Nodulation and growth of leucaena leucocephala (Lam.) de wit as affected by inoculation and N fertilizer - Sanginga, N.; Mulongoy, K.; Ayanaba, A. (1988)
Leonard jar, pot and field experiments examined the effects of inoculation and the influence of nitrogen fertilizer on nodulation, nitrogen fixation and growth ofLeucaena leucocephala (Lam.) de Wit at IITA, Ibadan, Nigeria. Leucaena responded to both inoculation and/or nitrogen application. Shoot growth and total N and P of inoculated plants were comparable to those of the highest N treatment, and the values were about 55% greater than those of uninoculated ones. Field data indicated that toal N yields of inoculated leucaena were increased by 50% with 40 or 80 kg ha−1 of N fertilizer. However, N fertilizer depressed N fixation by 56% as was expected from nodule mass data. N-fixation was delayed for about 8 weeks in the plots without N. Application of small amounts of N starter (20 ppm) proved to be beneficial to satisfy the plant need during the early stage of leucaena growth. The rhizobial strains IRc 1045 and IRc 1050 were effective, competitive and survived well in the field one year after their establishment.